Cost-effectiveness analysis of a multiple health behaviour change intervention in people aged between 45 and 75 years: a cluster randomized controlled trial in primary care (EIRA study) - Ignacio Aznar-Lou; Edurne Zabaleta-; Marc Casajuana-Closas; Alba Sánchez-Viñas; Elizabeth Parody-Rúa; Bonaventura Bolíbar; Montserrat Iracheta-Todó; Oana Bulilete; Tomàs López-Jiménez; Haizea Pombo-Ramos; María Victoria Martín Miguel; Rosa Magallón-Botaya; et al. (BMC, 2021)
Abstract Background Multiple health behaviour change (MHBC) interventions that promote healthy lifestyles may be an efficient approach in the prevention or treatment of chronic diseases in primary care. This study aims to evaluate the cost-utility and cost-effectiveness of the health promotion EIRA intervention in terms of MHBC and cardiovascular reduction. Methods An economic evaluation alongside a 12-month cluster-randomised (1:1) controlled trial conducted between 2017 and 2018 in 25 primary healthcare centres from seven Spanish regions. The study took societal and healthcare provider perspectives. Patients included were between 45 and 75 years old and had any two of these three behaviours: smoking, insufficient physical activity or low adherence to Mediterranean dietary pattern. Intervention duration was 12 months and combined three action levels (individual, group and community). MHBC, defined as a change in at least two health risk behaviours, and cardiovascular risk (expressed in % points) were the outcomes used to calculate incremental cost-effectiveness ratios (ICER). Quality-adjusted life-years (QALYs) were estimated and used to calculate incremental cost-utility ratios (ICUR). Missing data was imputed and bootstrapping with 1000 replications was used to handle uncertainty in the modelling results. Results The study included 3062 participants. Intervention costs were €295 higher than usual care costs. Five per-cent additional patients in the intervention group did a MHBC compared to usual care patients. Differences in QALYS or cardiovascular risk between-group were close to 0 (− 0.01 and 0.04 respectively). The ICER was €5598 per extra health behaviour change in one patient and €6926 per one-point reduction in cardiovascular risk from a societal perspective. The cost-utility analysis showed that the intervention increased costs and has no effect, in terms of QALYs, compared to usual care from a societal perspective. Cost-utility planes showed high uncertainty surrounding the ICUR. Sensitivity analysis showed results in line with the main analysis. Conclusion The efficiency of EIRA intervention cannot be fully established and its recommendation should be conditioned by results on medium-long term effects. Trial registration Clinicaltrials.gov NCT03136211 . Registered 02 May 2017 - Retrospectively registered